Validitas Pengembangan LKPD Menggunakan Model TTW pada Pembelajaran Tematik Terpadu di Kelas IV Sekolah Dasar - Sry Apfani (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
Based on the results of the preliminary analysis, it was found that the LKPD circulating in schools had not been able to direct students to study independently. This study aims to develop LKPD using the TTW model. The type of research used is the type of research and development (R & D), which uses a 4-D model. This model consists of 4 stages of development, namely definition, design, development, and dissemination. This research is only up to the stage of development that is to development. Data collection instruments in this study were used in the form of curriculum analysis sheets, student analysis, LKPD validation sheets (for linguists, material, and design experts). Based on the results of the LKPD validation using the TTW model, it is declared very valid. The level of validity of the design aspect is 90% with a very valid category, the level of validity of the material aspect is 91% with a very valid category, and the level of validity of the language aspect is 80% with a valid category, this shows that the LKPD product using the TTW model is at the category is very valid so that it can be used in integrated thematic learning.